The archaeology of everyday life at early Moundville - Wilson, Gregory D., 1969- (Dan Josselyn Memorial Publication., 2008)
Complex Mississippian polities were neither developed nor sustained in a vacuum. A broad range of small-scale social groups played a variety of roles in the emergence of regionally organized political hierarchies that governed large-scale ceremonial centers. Recent research has revealed the extent to which interactions among corporately organized clans led to the development, success, and collapse of Moundville. These insights into Moundville's social complexity are based primarily on the study of monumental architecture and mortuary ceremonialism. Less is known about how everyday domestic pra.